RANCANGAN SISTEM DINAMIS PERENCANAAN PENYEDIAAN DAN KONSUMSI BAHAN BAKAR MINYAK - Rohmatulloh Muhamad Ikhsanuddin; Alfiyanto, Muhammad Annas (Journal of Data Science Theory and Application, 2024)
The supply and consumption of fuel oil (BBM) is a crucial aspect in the global energy framework that affects the economy, environment and sustainability. In the era of climate change, the focus on energy sustainability drives this research to evaluate environmental impacts and efforts to reduce dependence on fuel. This research aims to predict future fuel supply and consumption. The model used in this research is a dynamic system model. The simulation results show that fuel supply and consumption will continue to increase until 2038. By exploring the relationships between variables in this system, it is hoped that this research can provide strategic insights for policy makers, industry and academics to design sustainable solutions, encourage innovation and face challenges. faced by future fuel supply and consumption.